Nursing handover of vital signs at the transition of care from the emergency department to the inpatient ward: An integrative review. Issue 5 (23rd October 2018) - Cross, Rachel; Considine, Julie; Currey, Judy
Abstract: Aim: To examine nursing handover of vital signs during patient care transition from the emergency department (ED) to inpatient wards. Background: Communication failures are a leading cause of patient harm making communication through clinical handover an international healthcare priority. The transition of care from ED to ward settings is informed by nursing handover. Vital sign abnormalities in the ED are associated with clinical deterioration following hospital admission. Understanding the role and perceived value of vital sign content in clinical handover is important for patient safety. Methods: An integrative design was used. A search of electronic databases was undertaken using MEDLINE, CINAHL, EMBASE, Cochrane, Web of Science and SCOPUS. Identified records were screened to elicit further studies for inclusion. A comprehensive peer‐review screening process was performed. Studies were included that described the surrounding issues of handover, vital signs, ED, transition of care and ward. Results: Five studies were included in the final review, one specific to nursing and four specific to emergency medicine. Vital signs were perceived to be an important inclusion in clinical handover, and the communication of vital signs in handover was perceived to be indicators for patient safety and risk factors for future clinical deterioration. The ED environment had an influence on effective communication within handover. Conclusions: Vital signs were an important inclusion for clinical handover. Deficiencies in vital sign content were perceived to be risk factors for patient adverse events following hospital admission. The quality of vital sign information in clinical handover may be important for accurate decision‐making. Relevance to clinical practice: Vital signs are an important component of clinical handover and are perceived to be indicators for patient safety and risk of future adverse events.